Dependence of the foaming window of a polystyrene/poly(methyl methacrylate) blend on structural evolution driven by phase separation. (12th March 2019) - Liu, Wei; Pang, Yongyan; Wu, Minghui; Qin, Kangpei; Zheng, Wenge
Abstract: The objective of the present work was to study the dependence of the foamability and the foaming window of a polystyrene/poly (methyl methacrylate) (PS60/PMMA40) blend on the structural evolution driven by phase separation. A compression molding machine was used to prepare the blend samples thermally annealing for various times. The phase contrast optical microscope (PCOM) and scanning electron microscopy (SEM) were used for phase morphological change study. The samples were foamed via a batch foaming process, and SEM was used for cell structure observation. The desorption curves of the blend samples were studied to show the dependence of the gas desorption diffusion coefficient on the annealing. It was found that the phase domain size was increased in a wide range with the annealing, and that the foaming behavior was significantly affected by the structural evolution for the blend with big phase domains and the saturation under high pressures. The gas desorption diffusion coefficient was increased for the interface with the phase domain, which resulted in the decreased expansion ratio after foaming, with varying reduction degrees for varying saturation pressures. Further, the suitable foaming temperature range was studied for the blend samples annealing for a short and a long period and saturated under each pressure. It was found that both the upper and the lower foaming temperatures were decreased with the saturation pressure, and the upper one was more vulnerable to the higher pressures for the blend samples after long-period annealing, leading to the much narrower suitable foaming temperature window. It was believed that the difference in viscoelasticity of the dispersed phase and the matrix was responsible for this phenomenon. Graphical abstract: Image 1017 Highlights: Foaming behavior is affected by structural evolution via phase separation. Phase domain size plays a significant role in affecting cell structure. Upper foaming temperature is vulnerable to large domain and high pressure. Foaming window is narrowed for combination of large domain and high pressure. Viscoelasticity difference of two phases affects foaming behavior significantly.